Carbon dioxide processing into alternative fuels - Salo, I.; Prosina, Kateryna; Просіна, Катерина Миколаївна; Просина, Екатерина Николаевна (ТДАТУ, 2018)
In recent years, mankind has faced climate warming on our planet as a result of changes in the composition of the atmosphere and the manifestation of the so-called greenhouse effect, keeping warmth on Earth. The higher the concentration of these gases, the greater the greenhouse effect
Keywords: greenhouse effect; climate warming; atmosphere; chlorofluorocarbons; solvents